2012
DOI: 10.1186/1742-9994-9-23
|View full text |Cite
|
Sign up to set email alerts
|

Development of the excretory system in a polyplacophoran mollusc: stages in metanephridial system development

Abstract: BackgroundTwo types of excretory systems, protonephridia and metanephridial systems are common among bilaterians. The homology of protonephridia of lophotrochozoan taxa has been widely accepted. In contrast, the homology of metanephridial systems – including coelomic cavities as functional units – among taxa as well as the homology between the two excretory systems is a matter of ongoing discussion. This particularly concerns the molluscan kidneys, which are mostly regarded as being derived convergently to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…The excretory organ of Helminthope resembles the paired larval/juvenile nephridia described recently in the chiton Lepidochitona Gray, 1821 [67,68]: these possess ‘larval’ protonephridia (with filter zone and vacuolated part) that become fully reduced, and ‘early adult’ protonephridia with an originally similar morphology that later becomes modified to form a metanephridial system after joining the pericardium. We assume that this mechanism is similar in heterobranch gastropods, including rhodopemorphs that possess only the (right) kidney as adults.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The excretory organ of Helminthope resembles the paired larval/juvenile nephridia described recently in the chiton Lepidochitona Gray, 1821 [67,68]: these possess ‘larval’ protonephridia (with filter zone and vacuolated part) that become fully reduced, and ‘early adult’ protonephridia with an originally similar morphology that later becomes modified to form a metanephridial system after joining the pericardium. We assume that this mechanism is similar in heterobranch gastropods, including rhodopemorphs that possess only the (right) kidney as adults.…”
Section: Discussionmentioning
confidence: 92%
“…As discussed above, the configuration of ganglia in Helminthope (except for the accessory ganglia) is highly similar to what Riedl [35] observed in 13 days old Rhodope , with still unfused visceral loop ganglia spread along the longitudinal body axis. Also, the lack of a heart (in mollusks developed shortly before metamorphosis, [108]) and therefore presence of only a protonephridial-type kidney (present before the heart; [68]) are early ontogenetic characters persisting in the adult. While heterobranchs are hypothesized to have evolved from an apogastropod ancestor in the centimeter size range by progenetic miniaturization and simplification especially of digestive and mantle cavity organs [18], rhodopemorphs have reduced body complexity even further parallel to their invasion of meiofaunal habitats accompanied by progenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Another frequently applied method of combining LM with TEM in the same specimen is alternating LM and TEM sectioning. Our own experience [23,24] has shown that LM re-sectioning is much more efficient, because alternating sectioning requires repeated changes of the equipment (e.g. knife, microtome) during sectioning and the number of sections to be examined with the TEM is significantly higher.…”
Section: Discussionmentioning
confidence: 99%
“…The muscular, vascular, excretory, and digestive systems were chosen for segmentation and surface rendering. The excretory organs were selected for the TEM investigation because their size relative to the entire specimen is typical for fine structural investigations, they bear complex ultrastructural details, and their detailed organization contributes information to ongoing studies on the nephrogenesis of molluscs [23,24]. …”
Section: Introductionmentioning
confidence: 99%
“…A espécie Leptochiton darioi (Righi, 1973) Heath (1905), Ashby (1929), Yonge (1932), Fretter (1938), Graham (1973, Boyle (1975Boyle ( ), ᴓkland (1980, Baxter & Jones (1981), Fischer (1988, Russel-Hunter (1988), Wanninger & Haszprunar (2002), Saito (2003), Sigwart (2008Sigwart ( , 2009, Vendrasco et al (2008), Schwabe (2010), Kodirov (2011), Baeumler (2012, Sigwart et al (2013Sigwart et al ( , 2014, Sigwart & Schwabe (2017).…”
Section: Seleção Dos Terminaismentioning
confidence: 99%